Study on Mechanical Behavior and Seepage Characteristics of Coal Mass during Unloading. (31st October 2021) - Wang, Yan; Han, Yongsheng; Liu, Fei
Abstract : With the increase of buried depth, the content of gas increases gradually. The gas in the mining process will lead to gas gush and other dynamic disasters, or even coal and gas gushing in front of the working face. Therefore, the study on the permeability distribution of coal and the surrounding rock is the core work of coal and gas mining at the same time. To study the mechanical behaviors and seepage characteristics of coal mass during unloading is to prepare for coal and gas mining in the future, which can not only ensure the safety of operators to the maximum extent but also increase the mining rate as much as possible. Based on the stress-strain curve and seepage curve, the brittleness index and seepage characteristics of coal are analyzed. The greater the brittleness index is, the more likely the coal mass is to produce cracks, and then to form large cracks, or even fracture. Through the study of brittleness index and seepage characteristics of coal mass, the mechanical behavior of coal mass can be easily obtained, so as to guide the mining of coal mass.